Simplified phenotyping of CYP2D6 for tamoxifen treatment using the N-desmethyl-tamoxifen/ endoxifen ratio. (December 2020) - Lee, Clara Inkyung; Low, Siew Kee; Maldonado, Ricardo; Fox, Peter; Balakrishnar, Bavanthi; Coulter, Sally; de Bruijn, Peter; Koolen, Stijn L.W.; Gao, Bo; Lynch, Jodi; Zdenkowski, Nicholas; Hui, Rina; et al.
Abstract: Introduction: CYP2D6 protein activity can be inferred from the ratio of N-desmethyl-tamoxifen (NDMT) to endoxifen (E). CYP2D6 polymorphisms are common and can affect CYP2D6 protein activity and E level. Some retrospective studies indicate that E < 16 nM may relate to worse outcome. Materials and methods: A target NDMT/E ratio was defined as associated with an E level of 15 nM in the 161 patient Test cohort of tamoxifen-treated patients, dichotomizing them into 'Normal' (NM) and 'Slow' (SM) CYP2D6 metabolizer groups. This ratio was then tested on a validation cohort of 52 patients. Patients were phenotyped based on the standard method (ultrarapid/extensive, intermediate or poor metabolizers; UM/EM, IM, PM) or a simplified system based on whether any variant allele (V) vs wildtype (wt) was present (wt/wt, wt/V, V/V). Comprehensive CYP2D6 genotyping was undertaken on germline DNA. Results: A target NDMT/E ratio of 35 correlated with the 15 nM E level, dichotomizing patients into NM (<35; N = 117) and SM (>35; N = 44) groups. The ratio was independently validated by a validation cohort. The simplified system was better in predicting patients without slow metabolism, with specificity and sensitivity of 96% and 44% respectively, compared with the standard method - sensitivity 81% and specificity 83%. Conclusions: The simplified classification system based on whether any variant was present better identified patients who were truly not CYP2D6 slow metabolizers more accurately than the current system. However, as CYP2D6 genotype is not the only determinant of endoxifen level, we recommend that direct measurement of endoxifen should also be considered. Highlights: We used a ratio of two tamoxifen metabolites to categorize CYP2D6 metabolizer groups. We developed a simplified system to identify slow metabolizers based on genotype. The simplified system was more accurate than the standard complex system.